Climatology of mixing layer height in China based on multi-year meteorological data from 2000 to 2013. (15th September 2019) - Zhao, Hujia; Che, Huizheng; Xia, Xiangao; Wang, Yaqiang; Wang, Hong; Wang, Peng; Ma, Yanjun; Yang, Hongbin; Liu, Yuche; Wang, Yangfeng; Gui, Ke; Sun, Tianze; et al.
Abstract: Atmospheric aerosol levels are high in different regions of China. Changes in atmospheric stability and mixing layer height (MLH) may affect the vertical aerosol distribution during pollution events. Here, we continuous studied the spatiotemporal distribution of MLH in China over 2000–2013 to characterize the regional-scale properties of atmospheric boundary layers. MLH was larger in the Southern Coastal and Southeastern China (1241.5 ± 73.5 and 632.7 ± 61.8 m, respectively), but lower in Eastern and Southwestern China (518.1 ± 63.6 and 462.7 ± 88.5 m, respectively). We divided the monitoring stations into 11 regions; these regions could be classified into three types with an increasing linear trend (95% confidence level), with a decreasing linear trend (95% confidence level), and with fluctuation changes. In all regions, MLH was higher in spring and summer than in autumn and winter. The spatial distribution of the diurnal MLH increased significantly at 1400 BJT (Beijing time) in all regions, with the strongest radiation being noted during the daytime. Higher levels of PM2.5 with corresponding lower MLH were noted during winter, indicating that lower MLH could confine the pollutant diffusion to near the surface. By contrast, in spring, higher MLH could be potentially due to the dynamic condition. In general, the poor air quality days occurred more frequently in winter than in other seasons. As the air quality worsened, most MLH showed a decreasing trend in almost all regions. This work provides information that aids in further understanding not only MLH distribution in China but also specific PM–MLH interaction to facilitate regional atmospheric environment monitoring and prediction. Highlights: Greater MLH was found in Southern and lower MLH in Southwestern China. The annual MLH with increasing/declining/fluctuating trends were found. Interaction between PM and MLH contributed to the regional air quality.